Balance of Interests as a Principle of Civil Law: Some Aspects of Legal Consciousness - SVIRIN, Yury Alexandrovich; KULAKOV, Vladimir Viktorovich; MOKHOV, Alexandr Anatolievich; SHESTOV, Sergej Nikolaevich; SOROKIN, Vladislav Petrovich (Journal of Advanced Research in Law and Economics, 2019)
The research considers the category of reasonable balance of interests in the context of civil relations. The authors of the article highlight the need to restrict permissibility as a method of civil regulation aimed at protecting the rights and interests of the weaker party in some legal relations. A reasonable balance of interests is ensured by laws and agreements, whose conditions become the subject of a judicial dispute in the absence of a mandatory rule. The authors have analyzed judicial acts conditioned by the need to maintain a reasonable balance of interests. As a result, they have determined that the first condition for applying the fair balance principle is the equivalence of counter-performance in the absence of both excessive benefits and excessive losses for the parties. The second condition is the party-related division in some civil relations. The authors have concluded that the risks of negative consequences should not be borne only by the weaker party if the latter could not reasonably foresee the consequences upon concluding the relevant agreement. Methods. The study is based on the comparative analysis of the Russian scientific doctrine and judicial practice. The main approach to the analysis of the legal tools in question is the method of system analysis. In addition, the authors used the structural-functional method and general scientific methods of cognition. The study aims at determining the principle of a reasonable balance of interests in civil law, its essence, necessity and expediency in the system of law enforcement. The authors aim to define conditions for applying legal norms to achieve a reasonable balance of interests among all parties in disputed legal relations. Results. The study results let the authors claim that the risks of negative consequences should not be borne only by the weaker party if it could not reasonably foresee such consequences upon concluding the agreement and the imbalance of interests among parties in civil-legal relations is caused by the violation by one or another party of the principles of fair practice and reasonableness . Although a reasonable balance of interests is a counterweight to the principles of contractual freedom and free will, courts should apply it to ensure the right of justice.